Contractual Savings or Stock Market Development—Which Leads? - Catalan, Mario; Impavido, Gregorio; Musalem, Alberto R. (World Bank, Washington, DC, 2015)
The authors study the relationship between the development of contractual savings (assets of pension funds, and life insurance companies) and non-life insurance, and, the development of stock markets (market capitalization and value traded). Their contribution lies in providing time-series evidence on a hypothesis that is very popular - but had not been substantiated - among supporters of fully funded pension systems in which funds invest large shares of their portfolios in tradable securities (equities, bonds). The literature is not clear on its assumption regarding causality between contractual savings, and capital market development. A one-way or two-way relationship is assumed, usually inter-changeably; the authors address the questions of which leads empirically. They present the evidence, including descriptive statistics, and the results of Granger causality tests, for OECD countries, and such countries as Chile, Malaysia, Singapore, South Africa, and Thailand. They do not present a theoretical framework, but do explain how the growth of the contractual savings sector, is thought to promote financial development. The authors find evidence in the data that causality between institutions, and markets either does not exist, or, if it exists, runs predominantly from institutions to markets. To a lesser extent, there is simultaneous causality between institutions, and markets. Furthermore, there is limited evidence that causality runs only from markets to institutions (the only exception seems to be for non-life insurance in developing countries). Results seem to support the idea that the development of institutional investors, is likely to promote the growth of market capitalization, more than that of value traded. In developing countries, there seems to be no causality from pension funds to growth in value traded, while there is causality from life, and non-life insurance.